2013
DOI: 10.1097/gox.0000000000000008
|View full text |Cite
|
Sign up to set email alerts
|

Breast Reinnervation

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 16 publications
(16 reference statements)
0
67
0
3
Order By: Relevance
“…Our respondents indicated that mainly their partner enjoyed their breasts during an intimate setting, however for this function erogenous sensation is not necessary. This might be clinically relevant, because technically we are able to perform a microsurgical nerve coaptation and restore breast sensation, light touch [ 6 ]. However, restoration of erogenous sensation is rather an exception [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our respondents indicated that mainly their partner enjoyed their breasts during an intimate setting, however for this function erogenous sensation is not necessary. This might be clinically relevant, because technically we are able to perform a microsurgical nerve coaptation and restore breast sensation, light touch [ 6 ]. However, restoration of erogenous sensation is rather an exception [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although excellent cosmetic results can be achieved with autologous breast reconstruction, most reconstructed breasts fail to regain sensation [ 5 ]. Technically, surgeons are able to perform a sensible nerve coaptation [ 6 10 ]. Currently, multiple randomized studies are on their way to provide level A evidence on the effect of nerve coaptation therefore it is not yet standard treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Female breast innervated by the lateral and anterior cutaneous branches of the intercostal nerves from the second to the sixth nerves which are scarified during breast mammaplasty [12]. Breast re-innervation is not done by most surgeons; they mainly depend on the regeneration of nerves from the adjacent residual post-mastectomy skin [13].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of sensation in the reconstructed breast has shown to improve patient satisfaction and quality of life [53]. The neurotization of abdominally based free tissue transfers have shown to have significantly increased sensory recovery [53,54]. Coaptation of the flap nerve is typically performed to the anterior branch of the third intercostal nerve (Figure 24).…”
Section: Adjunctive Procedures 91 Neurotizationmentioning
confidence: 99%
“…The benefits of using the anterior branch of the third intercostal nerve is minimal dissection needed and it is in the vicinity of the vascular anastomoses. A less commonly used donor nerve is the lateral cutaneous branch of the third or fourth intercostal nerve because it can be damaged with the mastectomy procedure and is far away from the flap pedicle [54]. If primary coaptation of the nerves is not possible, a nerve conduit or graft can be used to improve sensibility.…”
Section: Adjunctive Procedures 91 Neurotizationmentioning
confidence: 99%